A survey on blockchain cybersecurity vulnerabilities and possible countermeasures. Issue 2 (6th January 2019) - Hasanova, Huru; Baek, Ui‐jun; Shin, Mu‐gon; Cho, Kyunghee; Kim, Myung‐Sup
Summary: Blockchain technology has attracted considerable attention owing to its wide range of potential applications. It first appeared as a cryptocurrency, called Bitcoin, but has since been used in many other business and nonbusiness applications. Unlike most existing systems that are based on centralized frameworks, this new technology utilizes peer‐to‐peer networks and distributed systems which includes blockchain registers to store transactions. Its structure is designed as a digital log file and stored as a series of linked groups, called blocks. Each individual block is locked cryptographically with the previous block. Once a block has been added, it cannot be altered. Many security experts speculate that the inherent cryptographic nature of the blockchain system is sufficient to withstand constant hacking and security threats. However, previous studies on the security and privacy of blockchain technology have shown that many applications have fallen victim to successful cyberattacks. Owing to the increasing demand for cryptocurrency and its current security challenges, previous studies have not focused on blockchain technology cybersecurity vulnerabilities extensively. Here, our study extends upon the previous studies on vulnerabilities and investigates the types of potential attacks. Our study then provides further direction to highlight possible countermeasures against blockchain technology vulnerability to cybersecurity. Abstract : Study presents a review on security threats and vulnerabilities in existing cryptocurrency systems that include the possibility of attacks with a focus on issues related to user privacy and transaction anonymity. The real attacks on blockchain systems are investigated, and current possible countermeasure methods by attack types are discussed. Furthermore, practical and academic merits to enhance the security of blockchain and limitations of state‐of‐the‐art security solutions are summarized and discussed, and future directions in area of blockchain security are suggested.